KOMODIFIKASI AGAMA DALAM ISLAMIC TOURISM DAN AKTIVITAS EKONOMI - A. Zaenur rosyid (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2016)
The Background underlying of this research is the commodification process in the economic activities of sellers and visitors at the tomb of Sheikh Ahmad Mutamakkin complex. The Problems of this research is the process of commodification of religion in economic activity sellers and visitors in complex tomb of Syekh Ahmad Mutamakkin based on moral and rational behavior. Based on these problems, the goal of this research is the researcher wants to know how the behavior of the economy is going on, both the sellers (producer) as well as tourism of Islamic parties (the consumer). Based on data analysis has been conducted, the results of this study indicate that there are the moral and rational behavior in the economic activities of sellers and visitors at the tomb complex of Sheikh Ahmad Mutamakkin at the same time, which is contained in the motif of sellers and visitors, the network structure between the sellers and from the sellers and the buyer as well as their purchasing decisions. This shows the two perspectives of views between the moral and the economic behavior of a rational economy.